Features of primary and recurrent herpetic keratitis after COVID-19 infection - Дрожжина, Галина Іванівна; Середа, Катерина Віталіївна (My University, 2025)
Herpetic keratitis ( HK) is one of the most common infectious diseases of the cornea. Various triggering factors can be responsible for the reactiva- tion of Herpes simplex virus ( HSV): hypothermia, emotional, mental or temperature stress, as well as other viral diseases, including COVID-19 Purpose: To evaluate the features of the primary and recurrent herpetic keratitis after СОVID-19 infection. Methods: 83 eyes of 70 patients with herpetic keratitis after С ОVID-19 were analyzed. Patients were divided into two groups: I–with primary HK (30 eyes, 26 patients) and I I–with recurrence of H K (53 eyes, 44 pa- tients). According to the severity of the C OVID-19, three stages were dis- tinguished: mild (without pneumonia), moderate (with pneumonia, with- out intensive care), severe (with intensive care, artiﬁcial lung ventilation). In the venous blood of patients the levels of IgG antibodies to coronavirus spike protein; herpes virus type 1/2, Herpes Zoster virus, Cytomegalovirus, Epstein-Barr virus, and total vitamin D were determined. Results: In primary HK, dendritic epithelial (20.7 % compared with 2 % in recurrent H K), (χ2 = 6.5 (p = 0.02). and ulcerative-necrotic forms (41.2 % compared with 15.6 % in recurrent H K), (χ2 = 5.2 (р = 0.02) were more of- ten. Stromal non-necrotizing form was more common in patients with re- current HK (82.4 %) than in patients with primary HK (37.9 %), (χ2 = 14.3 (p = 0.0001). and was the most common form in both groups. Ulcerative- necrotic form was more often in patients with severe course of COVID-19. Bilateral HK was more frequently in group I I–9 patients (18 cases) com- pared to group I–4 patients (8 eyes). The level of I gG to HSV1-2 viruses was signiﬁcantly higher in patients with ulcerative-necrotizing H K compared to patients with dendritic epithelial (1.6 times) and stromal non-necrotiz- ing (1.5 times) keratitis. An increased level of I gG to Herpes Zoster was de- tected in 93.2 %, to Epstein-Barr virus–in 76.4 %, to Cytomegalovirus–in 86.4 % of patients. The level of vitamin D in venous blood was within the normal range in only 12.5 % of all examined patients. Conclusion: S ARS-CoV-2 infection can be a potential factor in HSV-1 re- activation and the development of both primary and recurrent HK, which are characterized by a higher incidence of bilateral eye lesions and stro- mal forms of H K. Ocular complication in cases of C OVID-19 infection can occur during the acute or recovery phase; it mostly occurs in severely in- fected patients.